Experimental In vitro Study to Assess the Antibacte-rial Activity of Thymus vulgaris Oil on Streptococ-cus Sanguinis - Shallal , Lubna F; Ahmed , Maha A (Journal of Baghdad College of Dentistry, 2022)
Background: The Streptococcus genus are the predominant bacteria in the mouth and the Streptococcus sanguinis is one of them which performing a primary function for expansion of dental biofilm. Gingival and periodontal disorders are caused by dental biofilm, today, there is a necessity to discover naturally presenting antibacterial compounds from herbs with less side effects as a substitutive to the commonly handled chlorohexidine. Thus, the purpose of this study was to assess the antibacterial activity of thymus vulgaris oil on Streptococcus sanguinis bacteria In vitro. Materials and Methods: Human supragingival plaque samples were taken from 10 subjects, then morphological and microscopical examination, biochemical tests, Optochin test, hemolytic ability test and conventional polymerase chain reaction test was applied to assure coincidence of Streptococcus sanguinis. The sensitivity of bacteria to Thymus vulgaris oil, the minimum concentration that inhibit the growth and killed the test bacteria were identified a partly as comparable to 0.2% chlorhexidine as a positive control and10 % dimethyl sulphoxide as a negative control. Results: Thymus vulgaris oil presented a significant antibacterial property on Streptococcus sanguinis with several grades of inhibition zones. When compared to Chlorohexidine, Thymus vulgaris oil had stronger antibacterial properties. The minimum concentration that inhibited the growth and killed Streptococcus sanguinis was (0.09%). Conclusion: Thymus vulgaris oil displayed higher antibacterial action with each concentration on Streptococcus sanguinis as compared to Chlorohexidine, therefore; it can be used as a natural substitutive oral health care product to Chlorohexidine.